Improving The Knowledge And Skills Of The Members Of The Limau Manih Mushroom Farmer Group About Diversification Of Processed Oyster Mushroom Products - Harlina Dewi, Kurnia; Meutia Fiana, Risa; Derosya, Vioni; Andhika Permata, Deivy; Hasbullah, Hasbullah; Awalina, Rahmi (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Mushroom Cultivation is one of the government programs aimed at triggering the economy of the people who need guidance not only in the cultivation of saj, but also requires guidance for processing into more economically valuable products. Low knowledge and skills of mushroom farmers about raw materials, processing technology and product packaging. The method of activities consists of the delivery of counseling material about the nutritional content and properties of oyster mushrooms, the delivery of material about the processing technology of various oyster mushroom based products, the delivery of material about product packaging and product manufacturing practices. The results of the activity showed an increase in the knowledge and skills of oyster mushroom farmers after the extension activities. Oyster mushroom farmers who initially did not know (score 1) became little know (score 2) and knew better and were very knowledgeable about various science and technology related to raw materials, processes and products (packaging)